2011
DOI: 10.1242/jeb.055186
|View full text |Cite
|
Sign up to set email alerts
|

Moment-to-moment flight manoeuvres of the female yellow fever mosquito (Aedes aegyptiL.) in response to plumes of carbon dioxide and human skin odour

Abstract: Odours are crucial cues enabling female mosquitoes to orient to prospective hosts. However, their in-flight manoeuvres to host odours are virtually unknown. Here we analyzed in 3-D the video records of female Aedes aegypti mosquitoes flying in a wind tunnel in response to host odour plumes that differed in spatial structure and composition. Following a brief (~0.03 s) encounter with CO(2), mosquitoes surged upwind and, in the absence of further encounters, counterturned without displacing upwind. These pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 59 publications
6
120
0
Order By: Relevance
“…In control experiments, in which we injected clean air instead of CO 2 , the female mosquitoes did not exhibit plume-tracking behavior (Figures 1c and 2a, Figure S1). In the presence of the CO 2 plume, the female mosquitoes showed stereotypical cast and surge behavior in response to CO 2 concentrations greater than 500–600 ppm (Figure S2), as has been reported previously [11, 18]. …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In control experiments, in which we injected clean air instead of CO 2 , the female mosquitoes did not exhibit plume-tracking behavior (Figures 1c and 2a, Figure S1). In the presence of the CO 2 plume, the female mosquitoes showed stereotypical cast and surge behavior in response to CO 2 concentrations greater than 500–600 ppm (Figure S2), as has been reported previously [11, 18]. …”
Section: Resultssupporting
confidence: 82%
“…This is particularly apparent for mosquitoes, which use a combination of olfactory, visual, and thermal cues to locate hosts [6–10]. Mosquitoes are thought to detect suitable hosts by the presence of a sparse CO 2 plume, which they track by surging upwind and casting crosswind [11]. Upon approach, local cues such as heat and skin volatiles help them identify a landing site [1215].…”
mentioning
confidence: 99%
“…Carbon dioxide activates and modulates the host-seeking behaviour of insects, including mosquitoes, in a concentration-dependent manner (Dekker et al, 2001;Guerenstein and Hildebrand, 2008;Dekker and Cardé, 2011). We have shown that a transient elevation of the background level of CO 2 significantly affects the behavioural response of the mosquitoes.…”
Section: Impact Of Elevated Co 2 Levels On Mosquito Behaviourmentioning
confidence: 91%
“…When a female mosquito in flight or resting on a walls inside a house comes in contact with a turbulent plume of CO 2 , she immediately turns upwind and increases speed or takes off in a process described as activation [12]. The CO 2 -receptor (Gr1, Gr2, Gr3) in the cpA neurons of the maxillary palps also detects whole-skin odor weakly [13], so when a female Aedes aegypti enters a plume of undiluted skin odor, she turns upwind and increases flight speed just as she does in a plume of CO 2 [12,14].…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 -receptor (Gr1, Gr2, Gr3) in the cpA neurons of the maxillary palps also detects whole-skin odor weakly [13], so when a female Aedes aegypti enters a plume of undiluted skin odor, she turns upwind and increases flight speed just as she does in a plume of CO 2 [12,14]. Diluted skin odor however is not sufficient to activate a mosquito or induce an upwind surge however it is highly attractive after a mosquito is activated by a momentary pulse of CO 2 , through mechanisms that are not well understood [12,14]. After activating upwind navigation the mosquito surges forward every time it contacts a CO 2 plume, closer towards the emitting source, and when contact is lost she casts across the direction of airflow maximizing chances of encountering another plume from the source [12].…”
Section: Introductionmentioning
confidence: 99%